Transient acute parkinsonism secondary to organophosphate poisoning:- Case report (European Journal of Health Research, 2024)
Although organophosphate poisoning presents a frequent clinical picture in different health services, the association with symptoms related to Parkinsonism is unusual, in initial stages they configure syndromic pictures such as acute cholinergic syndrome until its progression to more complex forms of polyneuropathies. We present the case of a 62-year-old male patient who, after ingesting organophosphates, developed a cholinergic syndrome until presenting transient manifestations of parkinsonism.
Keywords: Organophosphate Insecticides; Organophosphate Poisoning; Parkinsonian Disorders